Barriers to spectacle acceptance among secondary school students in Igabi, North-Western Nigeria - Sano, Bulus Stanley; Diyale, Sarki Pamela (International Journal Of Community Medicine And Public Health, 2020)
Background: The aim of this study was to determine spectacle acceptance and its barriers among secondary school students in Igabi, North-western Nigeria. Methods: In a students’ sample of 534, those with presenting VA < 6/9 in either eye that can be improved by 2 lines or more with refraction were identified. The students and their parents were provided with information on obtaining spectacles and its benefits. Two months later students were identified and assessed by direct inspection for purchase of spectacles and reasons for non- purchase were identified. Results: Thirty-four students out of 534 (6.4%) had refractive error with the age group of 16-18 years accounting for 204 (38%) of the study population. Only 14 (41.2%) of those requested to buy -spectacles bought. Among those who bought and use spectacles, 10 (71.4%) were females. Cost was responsible for 14 (70%) of spectacle non-purchase while extent of refractive error and various misconceptions on spectacle use were also determinants of spectacle purchase and use. Spectacle use was associated with subjective improvement in academic performance in 12 (85.7%) of those who bought and use spectacles. Conclusions: Cost of spectacles and various misconceptions on its use affect acceptance.